Efficacy and Safety of Tranexamic Acid in Aneurysmal Subarachnoid Hemorrhage: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Shi, Min; Yang, Chao; Chen, Zu-han; Xiao, Ling-fei; Zhao, Wen-yuan (Frontiers in Surgery, 2022)
Tranexamic acid has been shown to reduce rebleeding after aneurysmal subarachnoid hemorrhage; however, whether it can reduce mortality and improve clinical outcomes is controversial. We performed a systematic review and meta-analysis to evaluate the efficacy and safety of the tranexamic acid in aneurysmal subarachnoid hemorrhage. We conducted a comprehensive literature search of PubMed, Embase, Web of Science, and Cochrane Library from inception to March 2021 for randomized controlled trials (RCTs) comparing tranexamic acid and placebo in adults with aneurysmal subarachnoid hemorrhage. The risk of bias was evaluated using the Cochrane Handbook, and the quality of evidence was evaluated using the GRADE approach. This meta-analysis included 13 RCTs, involving 2888 patients. In patients with aneurysmal subarachnoid hemorrhage tranexamic acid had no significant effect on all-cause mortality (RR = 0.96; 95% CI = 0.84–1.10, p = 0.55, I2 = 44%) or poor functional outcome (RR = 1.04; 95% CI = 0.95–1.15, p=0.41) compared with the control group. However, risk of rebleeding was significantly lower (RR = 0.59; 95% CI = 0.43–0.80, p = 0.0007, I2 = 53%). There were no significant differences in other adverse events between tranexamic acid and control treatments, including cerebral ischemia (RR = 1.17; 95% CI = 0.95–1.46, p=0.15, I2=53%). At present, routine use of tranexamic acid after subarachnoid hemorrhage cannot be recommended. For a patient with subarachnoid hemorrhage, it is essential to obliterate the aneurysm as early as possible. Additional higher-quality studies are needed to further assess the effect of tranexamic acid on patients with subarachnoid hemorrhage.